Influence of Jakri Game on Elementary School Students’ Understanding and Interests on Word Problem: Using Realistic Mathematics Education - Peni, Nur Robiah Nofikusumawati (Department of Mathematics, Universitas Negeri Semarang, 2017)
This study aims to clarify the influence of Jakri game in improving students’ understanding and interest in learning word problem. By using Realistic Mathematics Education (RME) approach, the classroom is designed to support students to understand word problem. 81 students in Alor Regency, East Nusa Tenggara Province, were pointed out in order to reach the objectives of the data. This research used a quantitative method to measure students’ understanding and interest in learning word problem by playing Jakri. Based on the level of RME approach, many students are able to reach level 1, students easy to accustom with Jakri game (real situation level), but students have some difficult to shifting from level 2 to level 3 (model-of level to model-for level). No one of them can reach the formal mathematics level (level 4). Students also have difficulty to do computation but the students create new mathematics sentence based on their own story. The result based on the questionnaire which measures students’ interest in Jakri game shows that the students like the game which mean that they interested to this game and enjoy the mathematics class.